Evaluating Digital Transformation Effectiveness in Plantation Operational Administration Using a Framework Based Information System Approach - Dea Sevy Yana; Yustria Handika Siregar; Prihasti Prihasti (Bigint Computing Journal, 2026)
This study presents an empirical evaluation of the effectiveness of digital transformation of plantation operational administration, through the implementation of the LintraMax Plantation Director (LPD) system at PT. Tolan Tiga Indonesia – Pelabian Estate uses the Digital Transformation Framework (DTF). Different from previous research, which tended to be conceptual, this study was based on the implementation of real systems used operationally by five main administrative functions, namely Payroll Clerk, Material Clerk, Accounting Clerk, Production Clerk, and General Clerk. This study uses a descriptive qualitative method with data collection through observation, in-depth interviews, and documentation, which is analyzed using the Miles and Huberman model. The results of the study show that the application of LPD is able to increase work time efficiency, speed up the reporting process, and increase the consistency and accuracy of administrative data. Based on the assessment using the Digital Transformation Framework, the level of effectiveness of digital transformation is in the Good category, with the main strength in the technology and strategy dimensions, but still requires strengthening in the aspects of work culture and human resource development. The findings of this study provide an academic contribution in the form of empirical evidence of the application of the Digital Transformation Framework in plantation operational administration, as well as practical implications for plantation organizations in designing sustainable digital transformation.